2020
DOI: 10.1016/j.ijantimicag.2020.105974
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with plasma exchange followed by intravenous immunoglobulin in a critically ill patient with COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 8 publications
8
116
0
5
Order By: Relevance
“…These main results are in line with case reports describing recovery of deteriorating severely ill patients suffering from COVID-19 after initiation of IVIG treatment [7][8][9][10][11] and a small prospective open-label randomized clinical trial in the US showing in a patient subgroup with an alveolar-arterial gradient of >200 mm Hg at enrollment a lower rate of progression to mechanical ventilation requirement, shorter hospital and ICU stay and greater improvement in PaO2/FiO2 at 7 days when treated with the combination of IVIG and SOC than with SOC alone [16]. Our study also con rmed results of two retrospective cohort studies in China [12,13], one of which demonstrated IVIG to signi cantly reduce 28day mortality, to decrease in ammatory response, and to improve some organ functions in a subgroup of 103 critically ill patients only.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These main results are in line with case reports describing recovery of deteriorating severely ill patients suffering from COVID-19 after initiation of IVIG treatment [7][8][9][10][11] and a small prospective open-label randomized clinical trial in the US showing in a patient subgroup with an alveolar-arterial gradient of >200 mm Hg at enrollment a lower rate of progression to mechanical ventilation requirement, shorter hospital and ICU stay and greater improvement in PaO2/FiO2 at 7 days when treated with the combination of IVIG and SOC than with SOC alone [16]. Our study also con rmed results of two retrospective cohort studies in China [12,13], one of which demonstrated IVIG to signi cantly reduce 28day mortality, to decrease in ammatory response, and to improve some organ functions in a subgroup of 103 critically ill patients only.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, two marketed IVIG products were shown to react with SARS-CoV 2 antigens in vitro [6]. In line with all this, there have been case reports of COVID-19 patients who bene ted from IVIG treatment [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 83%
“…COVID-19 has been reported to arise from an in ammatory cytokine storm due to SARS-CoV-2 infection; therefore, suppression of the cytokine storm is a key approach for the treatment of patients with COVID-19. Extracorporeal treatment approaches have been used to remove in ammatory cytokines in patients with septic shock and ARDS, whereas several studies have reported the e cacy of PE, PMX-DHP and CHDF in patients with COVID-19 [10]. In the present case, three extracorporeal treatment approaches were utilised.…”
Section: Discussionmentioning
confidence: 94%
“…COVID-19 has been reported to arise from an in ammatory cytokine storm due to SARS-CoV-2 infection; therefore, suppression of the cytokine storm is a key approach for the treatment of patients with COVID-19. Extracorporeal treatment approaches have been used to remove in ammatory cytokines in patients with septic shock and ARDS, whereas several studies have reported the e cacy of PE, PMX-DHP and CHDF in patients with COVID-19 [8]. In the present case, three extracorporeal treatment approaches were utilised.…”
Section: Discussionmentioning
confidence: 94%